The pathway to employee retention: The impact of work stress, workload, and organizational culture with job satisfaction as a mediator - Agustin, Yuliana; Soegiarto, Dwi; Fahira, Keke Tamara (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2024)
This research aims to analyze the influence of work stress, workload and organizational culture on turnover intention through job satisfaction at PT Garudafood Putra Putri Jaya Tbk. This research is quantitative research. Data collection comes from the method of distributing research questionnaires. This research used a sample of 135 respondents. The population used in this research were employees of the partnership and raw material purchasing section of PT Garudafood Putra Putri Jaya Tbk. The data analysis technique for this research uses AMOS version 24 Structural Equation Modeling (SEM). The results of this study indicate that work stress has no effect on job satisfaction, workload has no effect on job satisfaction, organizational culture has no effect on job satisfaction, work stress has an effect on turnover intention, workload affects turnover intention, organizational culture affects turnover intention, and satisfaction work influences turnover intention. Job stress on turnover intention is greater than the indirect influence, workload on turnover intention is greater than the indirect influence, and organizational culture on turnover intention is greater than the indirect influence. Keywords: job stress, workload, organizational culture, job satisfaction, turnover intention